The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1051/e3sconf/202336504033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of pneumatic disc atomizer for low volume spraying

Abstract: The article presents the results of experimental studies to determine the dependence of the rotational speed of a pneumatic disc sprayer with coaxial air flow on the flow rate of the working fluid. To refine the parameters of the working body, studies were carried out within the liquid flow rate q, corresponding to the first and second spraying modes, at different rotation speeds ω, the working body's radius r, and the number of radial channels np. At the same time, the mass of the rotating part of the pneumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Leshko served as a scientific basis for the creation of reaping and harvesting machines for the harvested mass. It was revealed that during mechanized harvesting of testes, their significant losses are allowed due to easy crumbling [6][7].…”
Section: The Degree Of Knowledge Of the Problemmentioning
confidence: 99%
“…Leshko served as a scientific basis for the creation of reaping and harvesting machines for the harvested mass. It was revealed that during mechanized harvesting of testes, their significant losses are allowed due to easy crumbling [6][7].…”
Section: The Degree Of Knowledge Of the Problemmentioning
confidence: 99%
“…It should be noted that the most widely grown cotton species in the world is Gossypium hirsutum L. According to data provided by the U.S. International Agricultural Service in 2020, the Indian state has 13.4 million hectares which is 1/3 part of world cotton cropping area where the total cropping area is 32.94 million hectares worldwide. In India, the fiber yield equals to 487 kg per ha in comparison with worldwide where the average fiber yield is 775 kg per ha (Abdurakhmanov, 2021) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These include Afghanistan (27 th place), Turkey (32 nd place), Kyrgyzstan (38 th place), Portugal (41 st place) and Italy (44 th place). Other Central Asian states, Tajikistan and Kazakhstan, rank 51 st and 60 th , respectively, in the group with moderately high water shortages [3,4]. Turkmenistan is ranked in 15 th place (http://darakchi.uz/oz/112845).…”
Section: Introductionmentioning
confidence: 99%
“…Today, the soil in Uzbekistan warms up to 40-45 degrees during the day, and the temperature does not decline below 35 degrees at night. As a result of global climate change, conducting a number of scientific and research activities aimed at determining the impact of cotton varieties on water and nutrient requirements, growth and development, yield accumulation and changes in cotton fiber quality indicators is one of the urgent tasks of today [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this, the average annual temperature in Uzbekistan can be raised by 2-3 degrees in the north and by 1 degree in the south after 20 years. Climate change will lead to 10-15% more water evaporating from water surfaces and 10-20% more water being utilized as a result of increased plant transpiration and irrigation rates [3].…”
Section: Introductionmentioning
confidence: 99%